Congenital Candida krusei Sepsis in an Extremely Preterm Baby: Case Report and Literature Review - Francesca Cossovel; Silvia Nider; Jenny Bua; Elena Ghirigato; Monica Piccoli; Paolo Manzoni; Laura Travan (Antibiotics, 2025)
A preterm neonate born at 24 + 5 weeks gestation developed congenital Candida krusei sepsis, diagnosed via placental culture, axillary swab, and elevated beta-glucan levels. Although initial blood cultures were negative, continuous HeRo monitoring played a crucial role in the early detection of clinical deterioration, prompting timely antifungal therapy with amphotericin B followed by micafungin. This proactive approach, combining prompt diagnosis, HeRo surveillance, and tailored treatment, ensured a favorable outcome. Our case underscores the value of HeRo monitoring as an early warning tool in managing neonatal fungal infections.